(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Mining activities in the Iullumeden (Sokoto) basin is often heard of due to its prominence in artisanal mode of ransacking the Earth in search of minerals and metal of high economic values. The unabated demand in the growing post-industrial era have decimated any health impact that could be borne by the inhabitants of the mining communities. Dange-Shuni is an enclave of this basin that was covered in a bid to determine the gross alpha and beta radioactivity in domestic water in and around mining points. Water samples were collected and analyzed via Hidex 300 SL system of Liquid Scintillation Counting from a systematic sampling of fifteen mining points. The results indicate that both the gross alpha and beta radioactivity concentrations were in elevation with about 80% and 85% above the global limits of 0.5 and 1.0 . The results are good reasons to work hard in order to bring dose of radioactivity exposure to the inhabitants to as low as reasonably achievable (ALARA) being a mandate of WHO.